Strategi Pembelajaran Quick on the Draw untuk Meningkatkan Aktivitas dan Hasil Belajar Mahasiswa Pada Materi Interpolasi - Septi Dariyatul Aini; Sri Irawati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2019)
This research aims to determine the increase in student learning activities and outcomes after being taught by using the quick on the draw learning strategy in the interpolation material. This type of research is classroom action research with a qualitative approach. This research was conducted at Madura University and those who were the subjects of the study were fourth semester students of 2017/2018 academic year mathematics education. Data collection techniques used are observation and test methods. From the data analysis it can be concluded that: (1) student activity has increased from 3.20 (good category) in the first cycle to 3.76 (excellent category) in the second cycle, (2) student learning outcomes have increased from 42.86 in the first cycle then increased to 85.71% in the second cycle. From the results of this study it can be concluded that the application of quick on the draw learning strategies can improve student learning activities and outcomes in interpolation material.